Immune therapies for malignant mesothelioma. Issue 8 (August 2014) - Antoniu, Sabina Antonela; Dimofte, Gabriel; Ungureanu, Didona
<x xml:space="preserve">Abstract</x> Malignant mesothelioma (MM) is a rare disease which can develop in pleura, pericardium or peritoneum and in which the therapies available have limited efficacy and are associated with various side effects. Therefore, there is a need for more targeted and more effective therapies which are able to halt the disease progression. Among them immune therapies actively or passively directed against various structures of the MM cells seem to be particularly promising given their inhibitory potential demonstrated in both experimental and early clinical studies. Mesothelin in particular seem to be not only a biomarker of disease activity but also a therapeutic target. This review discusses the immune therapies currently investigated for MM.